Educação profissional no Ceará: políticas e práticas na efetivação dos centros vocacionais técnicos em cenários de reforma (1990-2010) - Xerez, Antonia Solange Pinheiro (2013)
This research investigates the policy of the Professional and Technological Education developed in the State of Ceara, emphasizing the conception of practice in the technic vocational centers (CVTECs), pointing out the unit which is located in the Cearense city of São Gonçalo do Amarante (SGM). It is articulated with the movement of the educational reformation in the decades of (1990-2010) and it does reflection in order to comprehend the aspects of the Professional Education, considering the, in the documents of the reformation, it has been done the reference to the processes of changing in the labor world, new technologies, easing and qualification to the work. Since 1995, under the influence of the neoliberals governments, it was enhanced the convergence with the directories of the international organisms to the strengthening of the professional qualification policies, in the view to attending the expanding of the main funds. Thus, the problematic which guides this research can be summed up in the following question: which directories and educational fundaments guide the policy of Professional Education from CVTEC (conception and practice)? The hypothesis is that the fundaments and directories which guide the pedagogical project and the Professional Educational practice from CVTEC derive from the Pedagogy of Competences, from the centralization of the labor world, from the learn to learn pedagogy, contextualization, outsourcing, practices innate of marketing, entrepreneurship and from the idea of the modularization to the Professional Education. This hypothesis is stressed considering in the authors who signalize a national policy consolidated by the Fernando Henrique Cardoso government, by introducing in the teaching public systems the same way of the private management of the Professional Education, in accordance of the local business requirements, practice which was consolidated in the LuizInácio Lula da Silva government and that it has been weakened in the Public Education. This study aims to understand how the Technological Institute CENTEC, which is the manager and the supporter of CVTEC, incorporated the principles of the reformation from the Professional Education in Brazil, since the 1990s, and how they reverberate in the teachers pedagogical practices in the São Gonçalo do Amarante CVTEC. The documental research used the legislation in force, the plans from the governments from the latest decades, the messages from those governments to the congress, documents about the Pecém Project, the Integrated Plan of Technological and Professional Education of the State of Ceara, besides the by-law, regiment and pedagogical proposal of the CVTEC Institute, which prosecutes judicial autonomy above CVTEC. The study points out an absence of supply of Professional Education in the state of Ceara until 1995, when it was implemented the Superior Science and Technological and Educational Secretariat (SECITECE). In force of the Federal Law 5.154/2004, it arose the units of CVTECs, offering technological courses to a vocational profile from the school region. In 2008, the government inaugurated an expanding network of high-school level technological courses on the integrated genre attached to the Basic Education Secretariat SEDUC and started to reduce the attending by SECITEC, transferring some units to the Federal Institute of Science and Technological Education of Ceara (IFCE)